Stabilizing uncertain steady states of some dynamical systems by means of proportional feedback - Tamaševičiūtė, Elena; Tamaševičius, Arūnas (Nonlinear Analysis: Modelling and Control, 2013)
A simple zero-order proportional feedback technique for stabilizing unknown fixed points is described. The technique employs either artificially created or natural stable fixed point to find the coordinates of the unknown unstable fixed point. Four physical examples have been investigated, namely the mechanical pendulum, the autonomous Duffing damped oscillator, the van der Pol oscillator, and the Lorenz system have been considered both analytically and numerically.
Keywords: control; steady states; proportional feedback